Distance Learning: New Challenges in the Teaching of German and Russian Languages for Specific Purposes - Aleksandra J. Gojkov Rajić; Marijana N. Paprić (Inovacije u Nastavi)
This exploratory research examines the possibilities of applying new teaching approaches and working methods in the acquisition of Russian and German languages in the pedagogical profession under specific conditions of distance learning in an online environment. The theoretical context in which the draft of this research is placed refers to the elements of theories that are the basis of the self-regulation of learning (Sternberg, Deci, Rijan, Bandura), among which motivational aspects are at the top of the list. The method of the systematic non-experimental observation, in which statistical analyses are a substitute for experimental controls, seeks answers to questions about the advantages and limitations of online teaching in foreign language learning. In the research, a convenient sample was used, which consists of 107 students of the Faculty of Education, University of Belgrade, with Teaching Departments in Vršac and Novi Pazar, and Vocational Education and Medical College in Vršac. For the purposes of the research, a Likert-type questionnaire (PONUSJ) was used, which refers to the general assessment of the success of using ICT, and especially to the use of ICT in independent learning of a foreign (German and Russian) language outside of class, then to specific language aspects and skills for which adoption and improvement of online teaching very suitable, to different forms of work that have proven to be particularly interesting and useful during online foreign language teaching, as well as to the forms of classroom interaction that are assumed to be less suitable for online foreign language teaching. The reliability of the instrument determined by Cronbach’s α coefficient is satisfactory (α = 87).